Exploring the neural presentation of rhythmic quranic recitations using functional brain connectivity - Aziz, Nurfaizatul Aisyah Ab (2024)
Neuronal oscillations provide temporal and spatial signals that interact with the neural network to coordinate distinct neural processes into a higher cognitive function. The low-frequency neuronal oscillations, i.e., theta (4 – 7 Hz) and alpha (8 – 13 Hz), were the focus of most studies studying the effect of listening to Quranic recitations. This was based on the notion that these oscillations indicate the calmness and relaxation effect induced when listening to the Quranic recitation. This present study expanded the role of neuronal oscillations to include the high-frequency gamma waves (30 – 80 Hz) and the theta and alpha waves for previously unexplored neural correlate of rhythmic Quranic recitations. Thirty (30) healthy participants (n = 15 Muslim, 15 = non-Muslim) were randomly recruited and subjected to simultaneous recording magnetoencephalography (MEG) and electroencephalography (EEG) (M/EEG) to record the brainwaves response during passive listening to three different Quranic recitation styles, i.e., Murattal Asim, Murattal Susi and Tarannum Asli of the Ayatul Kursi verse. Ayatul Kursi is the greatest verse in the Al-Quran, which has healing linguistic and rhythmic aesthetics. The recorded M/EEG data were pre-processed and analysed using Brainstorm software in MATLAB environment. The average volume source estimation of the neuronal oscillations was estimated from the 170 brain regions of the AAL3 atlas. Higher theta activities were found at the anterior cingulate cortex (ACC) and midcingulate cortex (MCC) in the Muslim group and hippocampus in the non-Muslim group. High alpha activities could be seen at the precuneus in both groups, indicating increased mind-wandering. Both groups also showed alpha activation in the brain regions correlated to the visual network, proposing visual mental imagery of the auditory stimuli. The central regions of the brain seemed to be activated in all auditory stimuli in both groups, indicating there were language and speech perceptions involved. The results emphasize that, despite the likely extent of familiarity differences to rhythmic Quranic recitation between the Muslim and non-Muslim groups, widespread brain activations were shown involving regions that have roles in emotion, cognition, empathy, memory processing, visual imagery and language perception. The majority of the brain regions where source estimations were made had shown significant correlations (p<0.05). Whole brain source-level functional connectivity of the M/EEG data was quantified using Phase Locking Value (PLV). There was significant theta phase synchrony between the right middle frontal gyrus (MFG) and the left angular gyrus (AG), points to the role of MFG in reorienting the attention, presumably from the shifting of attention from mind-wandering to focusing on the Quranic recitation. Meanwhile, synchronising the cerebellum and the regions at the inferior parietal lobule in theta and increased alpha synchrony at the central regions might point to language perception and processing of the phonological information. Functional connectivity at the visual and default mode networks (DMN) could also be seen in alpha and gamma oscillations. Furthermore, increased Rolandic operculum and ACC engagement in gamma oscillation correlate to a positive feeling when listening to the rhythmic Quranic recitation. To summarise, the current study is the first of its kind of theta, alpha, and gamma neuronal oscillations to show that listening to Quranic recitations with different rhythmic styles of Ayatul Kursi may represent the neural correlate that underlie the anecdotal claims reported to influence positive emotion, social cognition, empathy, attention, language perception, and memory processing with the evidence of the brain connectivity mapping.